The lite side - Koh, Deborah Ashley En Li (2017)
The Lite Side is a health communication campaign by four students from the Wee Kim Wee School of Communication and Information, Nanyang Technological University (NTU). The campaign aimed to increase the frequency that university students consume healthier meals on campus, and was executed in collaboration with the Health Promotion Board and National Youth Council in NTU and Singapore Management University.